Nonadiabatic scattering of NO off Au3 clusters: A simple and robust diabatic state manifold generation method for multiconfigurational wavefunctions. Issue 6 (28th December 2018) - Robertson, Christopher; González‐Vázquez, Jesús; Corral, Ines; Díaz‐Tendero, Sergio; Díaz, Cristina
Abstract : The presence of nonadiabatic effects during the interaction of small molecules with metals has been observed experimentally for the last decades. Specially remarkable are the effects found for NO/Au, where experiments have suggested the presence of very strong vibronic coupling during the molecular scattering. However, the accurate inclusion of the nonadiabatic effects in periodic boundary conditions (PBC) theoretical methods remain an unapproachable challenge. Here, aiming to give some theoretical insight to the strong vibronic coupling, we have adopted a pragmatic point of view, taking use of an auxiliary simplified system, NO/Au3 . We show the importance of nonadiabatic coupling, during the scattering of NO from a Au3 cluster, using a diabatic representation of 12 electronic states of the system, including a few charge‐transfer states. Our diabatic representation is obtained by rotating the orbital and configuration interaction (CI) vectors of a restricted active space (RAS) wavefunction. We present a strategy for extracting the best effective manifold of states relevant to the system, below some prescribed energy, directly from the RAS CI vectors. This scheme is able to disentangle a large dense manifold of adiabatic states with strong coupling and crossings. This approach is also shown to work for multireference configuration interaction (MRCI). By performing quantum propagations, we observed an increase in vibrational redistribution with increasing initial vibrational or translational energies. We suggest that these nonadiabatic effects should also be present at smaller energies in larger clusters. © 2018 Wiley Periodicals, Inc. Abstract : Diagram showing charge transfer and excited diabatic states along the scattering coordinate for Au3 + NO system. A gaussian wavepacket is propagated to measure the nonadiabatic vibrational redistribution present.